Determinants of Physicochemical Composition of Palm Oil Mill Effluent - Implications on Environment and Bio-digester Treatment Design - E.B. Tambe; A.U. Okonkwo; I. E. Mbuka-Nwosu; C.O. Cookey; E. Agbe; S.C. Onwusa; I.N. Ekpe; U.F. Evuen; J. Okpoghono (Applied Environmental Research)
Growing need for renewable energy and addressing challenges associated with indiscriminate wastes disposal has necessitated harnessing wastes to wealth. The study investigated parameters determining the physicochemical composition of palm oil mill effluent (POME) generated at Agricultural Development Authority Palm (ADAPALM) and palm oil mills in its catchment communities, located at Ohaji/ Egbema Local Government Area of Imo State, Nigeria and their implications on environmental health and treatment approaches required. Survey research design was used. From a randomly sampled small-scaled mill in each community, and for the lone medium and large-scaled mills, four homogenous samples of POME were collected from sampled small, medium and large-scaled mills for laboratory analysis of potential of hydrogen (pH), dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total carbon (TC), total solid (TS), total suspended solid (TSS), total organic carbon (TOC), total nitrogen (TN), total kjeldahl nitrogen (TKN), ammonia nitrogen (NH3-N), Manganese (Mn), Nickel (Ni), Iron (Fe), Copper (Cu), Chromium (Cr), Cadmium (Cd), Potassium (K), total phosphorus (TP), Calcium (Ca), and Magnesium (Mg) using standard methods for wastewater analysis as described in American Public Health Association. Data was analysed using multivariate analysis of variance, and showed that the physicochemical composition of POME was significantly different (p<0.01) across milling-scales, types of FFBs and seasons. The pH=11.728±0.467 and 4.10563±0.030, BOD= 52.042± 1.669 and 233.125±10.674; TSS=14421.748±2431.870 and 974.344±29.764; TN= 347.918±7.371 and 468.92500±31.315; TP=127.890±1.478 and 26.476±6.339 for dry and wet seasons respectively, and COD=3731.250±154.574 for dry season only were not within the acceptable wastewater discharge limits. The pH, Cd, Ni, Cu, K and organic content across seasons highlight specific concerns in the wastewater treatment. The study has simultaneously addressed a wider scope of independent variables that define the composition of POME, and required approaches necessary to revert environmental degradation and promote green energy access in the area.